(untitled) (Global Journal of Science Frontier Research, 2023)
High-resolution infrared absorption spectra of the H2CO•••HF complex and its monomers are recorded in a gas phase in C=O and C-H regions using Bruker HR 125 spectrometer recorded at 0.05 cm-1 resolution. After complex formation about the HF stretching band complicated shapes are not observed due to weak interaction couplings between C=O and C-H stretching of the H2CO•••HF complex. Also, quantum chemical calculations are performed in mp2//6311++g(3df, 3pd) approximation, and energetic, geometrical, and harmonic spectral parameters have been calculated.